Transitioning European protein-rich food consumption and production towards more sustainable patterns-strategies and policy suggestions - Manners, Rhys; Blanco Gutiérrez, I.; Varela Ortega, C.; Tarquis, A.M. (MDPI, 2020)
Global and European diets have shifted towards greater consumption of animal proteins. Recent studies urge reversals of these trends and call for a rapid transition towards adoption of more plant-based diets. This paper explored mechanisms to increase the production and consumption of plant-proteins in Europe by 2030, using participatory backcasting. We identified pathways to the future (strategies), as well as interim milestones, barriers, opportunities and actions, with key European stakeholders in the agri-food chain. Results show that four strategies could be implemented to achieve the desired future: increased research and development, enriched consumer education and awareness, improved and connected supply and value chains and public policy supports. Actions needed to reach milestones were required immediately, reinforcing the need for urgent actions to tackle the protein challenge. This study concretely detailed how idealized dietary futures can be achieved in a real-world context. It can support EU protein transition by informing policy makers and the broader public on potential ways to move towards a more sustainable plant-based future. The outputs of this analysis have the potential to be combined with dietary scenarios to develop more temporally explicit models of future dietary changes and how to reach them.